Characterization of membrane wetting phenomenon by ionic liquid via ultrasonic time-domain reflectometry (UTDR) - Huang, Ting-Yi (2021)
Ionic liquids (ILs) are becoming attractive solvents or catalysts in many industries, thus energy-efficient membrane-based technologies for the purification and concentration of ILs are gaining attention. Membrane wetting by ILs is recognised as the major challenge in membrane processes, but limited information is available. In this study, the dynamics of wetting of commercial hydrophobic polytetrafluoroethylene (PTFE) membranes by a water-immiscible IL, trihexyl(tetradecyl)phosphonium (THTDP), was characterized by an online and non-destructive technique – ultrasonic time-domain reflectometry (UTDR). In the UTDR analysis, information such as resistance of membrane to IL penetration, duration and rate of wetting process can be deduced from the changes in arrival time and amplitude of reflected peak from the IL/pore-air interface, i.e., pores in pristine hydrophobic membrane are completely-filled with air until IL penetration that displaces the pore-air. The UTDR analysis was further supported by offline and destructive methods typically used to characterize membrane such as Fourier-transform infrared spectroscopy (FTIR), contact angle (CA), liquid entry pressure (LEP) and field emission scanning electron microscopy (FESEM). Through the abovementioned analyses, it was concluded that the commercial hydrophobic PTFE membranes exhibited poor anti-wetting properties against concentrated THTDP IL due to chemical affinity between IL and membrane.